PENGARUH KECERDASAN EMOSIOAN DAN ROOT CAUSE ANALISYS TERHADAP KUALITAS LAYANAN PERHOTELAN - Salgangga, Selji; Fadilah, Mohamad Fazar; Nabila, Salma Putri; Widyanti, Putri (Universitas Boyolali, 2024)
The hotel industry, of course you must prioritize the quality of service to hotel guests to increase the company's competitiveness and improve the company's reputation. In its activities, it is very possible to find problems that must be immediately responded to or handled by the company management through the human resources within the company so that they can find best solution. Considering that the hotel industry is a business that provides services for lodging facilities and is closely related to the tourism sector, in carrying out its operations it must have reliable human resources and have good emotional intelligence so that it will influence the level of satisfaction of hotel guests or tourists who visit. In another dimension, an organization, including hospitality industry companies, will encounter problems in its operational activities which must be handled properly so as not to reduce the company's reputation. If it is not responded well, it is possible that the same problems will arise in the future. Therefore, companies, in this case business actors in the hotel industry, must implement or create a root cause analysis instrument, Root Cause Analysis, which aims to prevent the same problem from occurring again in the future so that it can reduce consumer satisfaction and reduce the company's reputation. Keywords: Emotional Intelligence, Root Cause Analysis, Service Quality